Oil wealth, corruption, and the multiple f(ph)aces of internal colonialism in Ahmed Yerima's Hard Ground - Lawal, Nurudeen Adeshina (Array, 2020)
This paper explores Ahmed Yerima’s play Hard Ground (2011) to show how Yerima employs dramatic elements to interrogate manifestations of corruption and internal colonialism engendered by violent struggles for oil wealth in the Niger Delta region. Some scholars from the Niger Delta region have alleged that Yerima’s Hard Ground falls short of being a “realistic” portrayal of the oil crisis in the Niger Delta. Their claim suggests that the play is an exercise in the service of the establishment. However, this study contends that Yerima’s representations of corruption and internal colonialism in the crisis are meant neither to underestimate the role of the establishment nor to overlook the suffering of the people in the region. The playwright’s portrayals of corruption and various forms of internal colonialism generating the oil crisis are informed by postcolonial, multiple, contradictory, and complementary realities/truths, which often reveal the complexities of socio-economic and political crises in the postcolonial African state. The study reveals that leadership egoism and failure are among the key factors that aggravate violent crises which recur in the region. In its conclusion, the paper asserts that the multiple insights that Yerima’s Hard Ground offers on the oil crisis call for collective efforts within the Niger Delta region in particular and Nigeria as whole at finding lasting solutions to the region’s crises orchestrated by the violent struggle for oil wealth.